MALAYSIA A MARITIME NATION - Ruhanas Harun (Maritime Institute of Malaysia (MIMA), 2023)
The notion of Malaysia as a maritime nation is not new. As a coastal state surrounded by significant bodies of water, Malaysia exhibits many characteristics of a maritime nation where peace, economic stability, and security are priorities in its rise and development. This book discusses Malaysia's aspiration of a maritime nation. It features various aspects of maritime sectors and will conclusively embark on a journey that would shape and rekindle interest in the concept of Malaysia as a maritime nation through literature, discussion, and research.